2020
DOI: 10.1007/s10072-020-04802-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-year macular volume assessment in multiple sclerosis patients treated with fingolimod

Abstract: Background Fingolimod (FNG) is associated with the development of symptomatic macular edema (ME) in a small subset of multiple sclerosis (MS) patients. By using spectral domain optical coherence tomography (SD-OCT), an increase in the total macular volume (TMV) was rarely detected during the first months of treatment.Objectives The objective of this study is to assess whether FNG treatment leads to long-term macular changes in a real-life setting. Methods Sixty RRMS patients starting FNG, according to therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Fingolimod was able to exert an anti-inflammatory action and to increase blood retinal barrier tight junctions expression in a rodent model of DR, by ultimately reducing vascular permeability (Fan and Yan, 2016). To this regard, it is worthy of note that the examination of fingolimod ocular effects in RR-MS patients showed a preserved macular structure and thickness over the time, together with a complete absence of macular edema, even if it is reported as a fingolimod side effect (Fruschelli et al, 2019;d'Ambrosio et al, 2020;Rossi et al, 2020). In our study, a virtual screening approach evidenced that fingolimod, along with other FDA already approved drugs, can bind with good-predicted affinity to melanocortin receptors MC1R and MC5R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fingolimod was able to exert an anti-inflammatory action and to increase blood retinal barrier tight junctions expression in a rodent model of DR, by ultimately reducing vascular permeability (Fan and Yan, 2016). To this regard, it is worthy of note that the examination of fingolimod ocular effects in RR-MS patients showed a preserved macular structure and thickness over the time, together with a complete absence of macular edema, even if it is reported as a fingolimod side effect (Fruschelli et al, 2019;d'Ambrosio et al, 2020;Rossi et al, 2020). In our study, a virtual screening approach evidenced that fingolimod, along with other FDA already approved drugs, can bind with good-predicted affinity to melanocortin receptors MC1R and MC5R.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fingolimod was able to reduce vascular permeability, increasing tight junctions expression in the blood retinal barrier (Fan and Yan, 2016). Additionally, several studies reported a preserved macular structure and thickness over time in RR-MS patients treated with fingolimod (Fruschelli et al, 2019;d'Ambrosio et al, 2020). Worthy of note, although macular edema is reported as a side effect of fingolimod administration with an incidence of 0.3-1.2% (Nolan et al, 2013), two studies evidenced that RR-MS patients treated with fingolimod did not show any case of macular edema (Fruschelli et al, 2019;Rossi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence for macular edema in real-life settings is about 1%, with good clinical outcomes after discontinuation of the medication [ 74 ]. Moreover, fingolimod mildly increases total macular volume in the general population [ 75 , 76 ].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%